Prof. Yaroslav Saliy celebrate 60 anniversary - PCSS, Editorial Board (Physics and Chemistry of Solid State, 2021)
SALIY Yaroslav Petrovych, Professor of the Physics and Chemistry of Solids Department at the Vasyl Stefanyk Precarpathian National University, Doctor of Physical and Mathematical Sciences, Professor, Permanent Participant of the International Conferences on Physics and Technology of Thin Films and Nanosystems and Editor of the Journal "Solid State Physics and Chemistry"